Recommendations for management strategies for children with inflammatory bowel disease during the epidemic of new coronavirus (COVID-19) infection - Ran Ao; Wen-Wen Kong; Xiao Deng; Shao-Ming Zhou; Zhao-Xia Wang (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
The novel Coronavirus, COVID-19, is highly infectious is mainly transmitted from an infected person through liquid droplets. Most patients have a good prognosis, a few patients are in critical condition. Children's infections are relatively mild, without fever and pneumonia and since they have the characteristics of clustering onset, they are easy to miss diagnosis and are thus more likely to cause disease transmission. Children with inflammatory bowel disease need to travel to and from the hospital multiple times to receive treatments due to this disease's own characteristics, which in turn increases their risk of infection. Therefore, management recommendations for children with inflammatory bowel disease through a network platform during the pandemic of COVID-19 infection are proposed.